Adoption Issues in DevOps from the Perspective of Continuous Delivery Pipeline - Muhammad Zulfahmi Toh, Abdullah; Shamsul, Sahibuddin; Mohd Naz’ri, Mahrin (ACM Digital Library, 2019)
DevOps and Continuous Delivery (CD) are the terms that are always related to each other in Software Delivery and Operation Process area. DevOps introduces a significant agile perspective to deliver the software product in short cycle time that will reduce technical debt that is caused by delay. Continuous Delivery is one of the DevOps' practices that enables software organization to release new features and new products rapidly. However, the correct practices are still in ambiguity to the current CD process. This paper investigates the advantages and limitation of DevOps adoption to improve the CD process. A qualitative web survey has been conducted to identify the DevOps and Continuous Delivery advantages and adoption problems. 13 respondents' feedbacks have been collected and analyzed. Based on the survey, there are four significant DevOps' practices that need to be considered and developed as a proper guideline to introduce to practitioners.